2007
DOI: 10.1007/s10593-007-0098-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cytotoxicity of metal 4-methyl-8-quinolinethiolates

Abstract: It has been shown that the introduction of a methyl group at position 4 of the quinoline ring in metal 8-quinolinethiolates brings about a significant increase in the selectivity of their cytotoxic activity. It was found that rhodium 4-methyl-8-quinolinethiolate is 46 times less toxic than the unsubstituted 8-quinolinethiolate but with comparable toxicity towards MG-22A tumor cells (LC 50 2 µg/ml).Many organic derivatives of copper [1], ruthenium [2], rhodium [3], and palladium [4] containing a metal to sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This is most markedly seen in the toxicity of the iridium complex 2c with a methyl group at position 5 (LC 50 220 µg/ml, LD 50 1785 mg/kg). The toxicity of the iridium and rhodium complexes with a methyl group at position 4 (LC 50 85 and 78 µg/ml respectively) are also an order less than toxicity of the complexes with the unsubstituted ligand [23]. The 5-methyl derivatives of iridium and osmium proved to be the least toxic while the 4-isomer was the least toxic of the rhodium derivatives.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…This is most markedly seen in the toxicity of the iridium complex 2c with a methyl group at position 5 (LC 50 220 µg/ml, LD 50 1785 mg/kg). The toxicity of the iridium and rhodium complexes with a methyl group at position 4 (LC 50 85 and 78 µg/ml respectively) are also an order less than toxicity of the complexes with the unsubstituted ligand [23]. The 5-methyl derivatives of iridium and osmium proved to be the least toxic while the 4-isomer was the least toxic of the rhodium derivatives.…”
mentioning
confidence: 94%
“…However, all of these compounds showing high activity towards tumor cells are also toxic to normal NIH 3T3 mouse embryonic fibroblasts [22]. The toxicity of the highly active rhodium and iridium 8-quinolinethiolates can be markedly decreased by the introduction into their molecules of a methyl group at the 4 position of the quinoline ring [23]. It was also found that substituents in different positions of the quinoline ring can increase the selectivity of action of di(8-quinolyl) disulfides [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several rhodium complexes have revealed a greater toxicity towards A549 lung carcinoma and T47D mammary gland cells than their ruthenium analogs [22] and this points to the promise of novel antitumor agents amongst rhodium compounds [23][24][25][26]. A series of osmium complexes has also shown comparable cytotoxicity towards various tumor cells [22,[27][28][29][30][31] We have found that iridium complexes [32][33][34][35] as well as those of ruthenium, rhodium, and osmium show a high cytotoxicity towards human fibrosarcoma HT-1080 and mouse hepatoma MG-22A cells with the use of 8-quinolinethiol [32][33][34] or 8-quinolineselenol [35] as ligand. Certain polypyridyl complexes of iridium actively inhibit the growth of human MCF-7 (mammary gland cancer) and HT-29 (large intestine cancer) tumor cells [36].…”
mentioning
confidence: 99%
“…The toxicity of the complexes can be varied by the introduction of a substituent into the quinoline ring [35,51] but, as in the case of analogous 8-quinolinethiolates [32][33][34], the selectivity of the substituent is low.…”
mentioning
confidence: 99%